2020
DOI: 10.1111/ans.16248
|View full text |Cite
|
Sign up to set email alerts
|

Random colonic biopsies in macroscopically normal colonoscopies: is there any benefit? A two‐centre audit of current practice

Abstract: Background: Recent guidelines from the British Society of Gastroenterology published in April 2018, recommended performing random colonic biopsies (RCB) in endoscopically normal colonic mucosa when investigating chronic diarrhoea in adults to rule out microscopic colitis; however, cost effectiveness was not accounted for due to poor evidence base. There is now more evidence that RCBs are of low yield and of significant cost. Methods: A two-centre audit of current practice was conducted at Rockingham General Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Therefore, a full ileocolonoscopy with biopsy sampling of the right hemicolon (one biopsy from the ascending colon and one biopsy from the transverse colon) and left hemicolon (one biopsy from the descending colon and one biopsy from the sigmoid colon) should be performed [11,12]. The biopsies from the right and left hemicolon should be placed in separate containers and labelled as such [7][8][9][10][11][12][13][14]. 4 Inflammatory bowel disease…”
Section: Recommendationmentioning
confidence: 99%
“…Therefore, a full ileocolonoscopy with biopsy sampling of the right hemicolon (one biopsy from the ascending colon and one biopsy from the transverse colon) and left hemicolon (one biopsy from the descending colon and one biopsy from the sigmoid colon) should be performed [11,12]. The biopsies from the right and left hemicolon should be placed in separate containers and labelled as such [7][8][9][10][11][12][13][14]. 4 Inflammatory bowel disease…”
Section: Recommendationmentioning
confidence: 99%
“…Furthermore, 85.4% of the total expenditure of our cohort of patients primarily resulted in patients either being discharged or receiving symptomatic management. A recent two-centre study which specifically critiques the guidelines published by the British Society of Gastroenterology found that of the 872 colonoscopies performed, only 1.5% random colonic biopsies yielded the diagnosis of microscopic colitis [ 12 ]. The calculated cost per positive diagnosis of microscopic colitis was $10 862.42, leading them to believe that this was not a cost-efficient diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%